PKM-Basic Education in Financing Management Student Organization in Providing Quality Services for Students in Islamic Boarding Schools - Moh. Rifa’i; Muhamad Fajar; Ahmad Khoirul Anwar; M. Imron Zahroni; Ahmad Sakir; Bashori Alwi; Ahmad Madadi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Quality services certainly require relevant costs and are managed through targeted financing management which has implications for providing quality services. Costs are allocated to priority programs within a certain time in a targeted manner. This service is carried out using a PAR (Participatory Action Research) approach strengthened by field survey methods, analysis of problems developing in the field, FGD (Focus Group Discussion), SWOT analysis, direct action by participants in the field related to cultivation management which can have implications for improving quality services for students. The service program is carried out by implementing field surveys with participants regarding conditions developing in the partner institution environment, then reinforced with FGD (Focus Group Discussion) related to service program priorities that need to be prioritized according to the partner's quality. Then the third step is to strengthen it with the activity of preparing basic financing management workshop materials for santri organizations in order to provide quality services for all santri who live in Islamic boarding schools, and ending with a basic financing management workshop for santri organizations by presenting all the sections involved in a student organization that directly provides services to all students according to their respective work focus